An architecture for power substations communication networks based on SDN and virtualization paradigms (2021)
ABSTRACT : The deployment of infrastructures related to the Smart Grid concept introduces data communication networks in the grid operation systems (control, communication, and monitoring). The implementation of data communication networks facilitates and improves the efficiency of the tasks related to the generation, transmission, and distribution of electrical energy. In turn, network management is being permeated by new technologies such as Software Defined Networking (SDN) and network virtualization, that promote automation and innovation of communication networks aiming to overcome the lack of flexibility and the difficulties to evolve that are present in current communication networks. In this context, this paper proposes a reconceptualization of the power substations communications network architecture based on the IEC 61850 standard. Here, we present a complete view of the Smart Solution for Substation Networks (S3N) architecture, which allows modeling the future power substations communication networks taking advantage of the benefits introduced by SDN and virtualization technologies. In addition, in order to provide a better understanding of the challenges arising in this area, and to generate new research interest in this field, a review of several studies oriented to determine the feasibility of incorporating SDN as a key element to improve the management and operation of the power substations communication networks is presented.